SOCIAL RIGHTS THROUGH TAX EXPENDITURES: CONTROL, EFFICIENCY AND EQUALITY ISSUES - Menezes Breyner, Frederico (Novos Estudos Jurídicos, 2021)
Contextualização do tema: the main topic of this paper is the use of tax law as a tool to promote social rights by way of tax expenditures rules. Objetivos: the objective is to analyze, through doctrinal and institutional legal research, whether these issues imply disapproval or recommendation of the use of tax law for this purpose. Metodologia: the method of the tax expenditure analysis allows to link tax law and social rights by relating tax breaks and public expenditures. Considering that the main dimension of social rights corresponds to a positive duty to provide goods and services to guarantee social welfare, the use of tax expenditures to fulfill this duty poses challenges in terms of efficiency, control, and equality. Resultados: the result is that that these challenges do not always point at tax expenditures as a poor tool to promote social rights. The argument of this paper is that the merits of tax expenditures depend on its design by legislators considering the adopted tax base (direct taxation on income or indirect taxation on consumption) and on the presence of other mechanisms to ensure tax equality.